Evaluating the protective role of ischaemic preconditioning in rat hearts using a stationary small-animal SPECT imager and (99m)Tc-glucarate - Liu, Zhonglin (2008)
OBJECTIVE: To examine the protective role of ischaemic preconditioning (IPC) in rat hearts using (99m)Tc-glucarate (GLA) and a stationary SPECT imager, FastSPECT. METHODS: Twenty-four rats with 30 min myocardial ischaemia and 150 min reperfusion (IR) were studied as follows. The IPC group (n = 6) underwent IPC (five cycles of 4 min ligation of the left coronary artery and reflow) before IR. The control group (n = 7) was treated by IR without IPC. The SPT group (n = 6) was subjected to IPC and an adenosine antagonist, 8-(p-sulfophenyl)-theophylline (SPT). The vehicle group (n = 5) received IPC and SPT carrier vehicle. GLA was delivered intravenously 30 min post-reperfusion, and 2-h dynamic cardiac images were acquired by FastSPECT. RESULTS: GLA showed ‘hot-spot’ accumulation in the ischaemic area-at-risk (IAR) and exhibited lower retention (% 5 min peak) in the IPC and vehicle groups (33.8 ± 2.6 vs. 35.7 ± 9.2, P>0.05) than in the control and SPT groups (63.1 ± 5.3 vs. 54.8 ± 4.8, P>0.05). The infarct size (% IAR) was larger in the control and SPT groups (48.2 ± 6.3 vs. 41.7 ± 6.3, P>0.05) than that in the IPC and vehicle groups (21.0 ±1.9 vs. 19.1 ± 4.6, P>0.05). In terms of the ex-vivo IAR-to-normal radioactivity ratio, there was a statistical difference between the control and IPC groups (7.4 ± 0.9 vs. 3.0 ± 0.4), as well as the SPT and vehicle groups (7.4 ± 1.0 vs. 3.4 ± 0.5). CONCLUSION: IPC offers cardioprotection and relates to the activation of adenosine receptors in rat hearts. FastSPECT GLA imaging is not only useful in detecting early ischaemia–reperfusion injury, but also valuable in evaluating cardioprotection.